Lessons from UK prospective diabetes study. - Turner, R; Holman, R (1995)
Type II diabetes is a major cause of morbidity and mortality, both from an increased risk of developing cardiovascular disease and from specific diabetic complications. At present, patients are often treated to prevent marked hyperglycaemia, that induces symptoms such as thirst. Moderately raised glucose levels are then accepted. At present, it is uncertain whether Type II diabetes should be treated more intensively, with diet, tablet or insulin therapy to maintain near-normal glucose levels, in order to prevent the onset of complications. The Diabetes Control and Complications Trial (DCCT) in insulin-dependent diabetic subjects with a mean age of 27 years has indicated that intensive therapy to achieve a haemoglobin A1c level of 7.1%, compared with 9.0% in a 'standard control group', will retard the progress of diabetic microvascular disease. It is not known whether this is similarly beneficial in Type II diabetic subjects, where the main complication is cardiac disease, or whether the even better control that can be obtained with pharmaceutical therapy in Type II diabetic patients would be worthwhile. It is similarly not known whether treatment with sulphonylurea, metformin or insulin is particularly beneficial or whether any of these therapies is potentially harmful. The UK Prospective Diabetes Study (UKPDS) has randomly allocated 4209 newly diagnosed Type II diabetic patients to different therapies and is determining: (a) whether improved glucose control will delay the onset of clinical complications; and (b) whether any specific therapy has advantages or disadvantages.